DOI: 10.1007/978-3-540-73589-2_9
|View full text |Cite
|
Sign up to set email alerts
|

On the Impact of Aspectual Decompositions on Design Stability: An Empirical Study

Abstract: Although one of the main promises of aspect-oriented (AO) programming techniques is to promote better software changeability than objectoriented (OO) techniques, there is no empirical evidence on their efficacy to prolong design stability in realistic development scenarios. For instance, no investigation has been performed on the effectiveness of AO decompositions to sustain overall system modularity and minimize manifestation of ripple-effects in the presence of heterogeneous changes. This paper reports a qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
222
1

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(232 citation statements)
references
References 27 publications
4
222
1
Order By: Relevance
“…The advocates of AOP claim that the refactored versions of Telestrada [8,16], Pet Store [8,16] , CVS Core Plugin [8,16], EImp Plugin [8], Health Watcher [19,36], and Prevayler [18] exhibit lower coupling. However, they take into account only a subset of the dependencies that generate coupling in AO systems.…”
Section: Table 2 Results For Size Coupling and Cohesion Metricsmentioning
confidence: 99%
See 3 more Smart Citations
“…The advocates of AOP claim that the refactored versions of Telestrada [8,16], Pet Store [8,16] , CVS Core Plugin [8,16], EImp Plugin [8], Health Watcher [19,36], and Prevayler [18] exhibit lower coupling. However, they take into account only a subset of the dependencies that generate coupling in AO systems.…”
Section: Table 2 Results For Size Coupling and Cohesion Metricsmentioning
confidence: 99%
“…AOP emergenced as a new paradigm to modularize the concerns whose implementations would otherwise have been spread throughout the whole application, because of the limited abstractions of the underlying programming languages. Since then, several studies [15,16,17,19,35,36] have suggested that AOP is successful in modularizing crosscutting concerns. Unfortunately, these studies either wrongly identify modularization with the lexical SoC offered by AOP, or wrongly measure coupling in AO systems.…”
Section: Motivations and Goalsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of pure code-level approaches have also shown that AO source code may improve certain software qualities (e.g. [30,31]). Obviously, this approach will not work if OO source code is required.…”
Section: Interspace Compositionsmentioning
confidence: 99%